Utilising Malaysian Fibre in Stone Mastic Asphalt as a Replacement of Imported Fibre - Muniandy, Ratnasamy; Vasudevan, Jeyan; Megat Mohd Noor, Megat Johari; Omar, Husaini (Universiti Putra Malaysia Press, 2001)
Stone Mastic Asphalt (SMA) technology is currently used in many countries. This is a gap grade mix with a high percentage of coarse aggregates. As such there is a tendency for the binder in the gap-graded mix to drain down during the hot weather that may cause premature failure of the mix. Various fibre types have been used successfully in SMA. However, the overall cost of the mix tends to be much higher than that in conventional mix. This paper looks into the suitability of the Malaysian fibre for the use in SMA. The fibre is analysed and compared with traditional European fibre that is commonly used in SMA. Several experiments on the fibre have been done including Fibre Drain Down Test and Morphological analysis using the Scanning Electron Microscope (SEM). Besides this, chemical analysis was also carried out with a variation of cellulose content, particle size and Gas Chromatograph analysis. The result of the preliminary analysis shows that Malaysian fibre has the potential to replace the imported traditional fibre.